Tackle the Meckel: laparoscopic diverticulectomy for a retained ingested foreign body—a case report - Marbun, Vania Myralda Giamour; Fadhilah, Azzahra; Allo, Kezia Nathania Limbong; Ghufron, Ahmad Aulia; Ismet, Mohammad Febriadi; Nagib, Faris; Rowika, Karl Heinz Leonhardt; Mazni, Yarman (Frontiers in Medicine, 2025)
We report a 16-year-old female who ingested a headscarf pin that remained in the gastrointestinal tract for three weeks. Imaging suggested its presence in the distal ileum, and laparoscopy with fluoroscopy identified the pin lodged in a Meckel’s diverticulum. A hybrid laparoscopic-assisted diverticulectomy was performed, with uneventful recovery. This case emphasizes considering Meckel’s diverticulum in prolonged foreign body retention, as it may be missed on standard advanced imaging, and the value of minimally invasive surgery for definitive management.